Memory and Loss as Urban Resistance: Spatial Discontinuity and the Afterlife of Bairro do Relógio - Santos, D.; Cordeiro, Graça Índias (VI Midterm Conference of ESA RN37- Overlooked Urban Narratives and Shifing Centralities, 2025)
This paper investigates how memory and loss shape urban identity in the aftermath of spatial discontinuity, focusing on the case of Bairro do Relógio, a Lisbon neighborhood demolished nearly thirty years ago. Originally constructed in the 1960s to temporarily house families displaced by infrastructural development, the neighborhood was never meant to endure. Yet for its former residents, it remains a vital emotional and symbolic territory. rounded in urban ethnography, archival research, interviews, and digital fieldwork, the study explores how memory becomes a means of countering the loss of physical space. Since 2011, former residents have used online platforms and community gatherings to reanimate the shared experience of place, reconfiguring belonging through acts of remembrance. These practices do not merely recall the past; they actively resist the erasure of collective identity. In this context, memory and loss are not opposites, but co-constitutive forces: loss provokes the activation of memory, and memory gives meaning to loss. Together, they produce a narrative continuity that challenges the rupture caused by demolition. This case reveals how the affective and social dimensions of memory can reconstruct urban identity even in the absence of built space. et against the broader backdrop of Lisbon’s urban redevelopment and displacement dynamics, this paper, based on a master dissertation (Santos, 2024) offers insight into how marginalized communities preserve their histories and negotiate symbolic survival. It calls for renewed attention to memory work as a response to spatial fragmentation and as a form of everyday urban resilience.